Pengaruh Peran Penyuluh Pertanian terhadap Tingkat Produksi Usahatani Jagung - Novianda Fawaz Khairunnisa; Zumi Saidah; Hepi Hapsari; Eliana Wulandari (Department of Communication and Community Development Sciences and PAPPI (Perhimpunan Ahli Penyuluhan Pembangunan Indonesia), 2021)
Agricultural extension agent’s have a strategic role in helping to increase maize farming production in Nunuk Baru Village, Maja District, Majalengka Regency. Agricultural extension play a role in guiding farmers in managing their farms effectively and efficiently to improve farmer welfare. Nunuk Baru Village is one of the corn-producing areas that has received more attention in agricultural extension activities. This study aims to identify the role of agricultural extension for maize farmers and to determine the effect of the role of agricultural extension on the level of maize farming production. The research design used is a quantitative approach with a survey method with 80 corn farmers as respondents. The method of data analysis in this study used descriptive analysis using a sematic differential scale and regression analysis. The results of this study indicate that the role of agricultural extension agent’s in Nunuk Baru Village, Maja District, Majalengka Regency is categorized as very good in carrying out their duties as a catalyst, communicator, consultant and organizer while as a motivator, educator and facilitator are categorized as good. The role of agricultural extension agent’s has no effect on corn farming production in Nunuk Baru Village.